Undang-undang tort: liabiliti bagi perbuatan rebakkan HIV secara seksual - Hashim, Marina; Abd. Rahim, Anita (UKM Press, 2013)
Tort law is a mechanism used to obtain damages for injuries suffered by a person. HIV-related tort litigation's at the beginning of this epidemic have focused on the defendants who are insured or have the financial capacity to pay compensation to the injured plaintiffs.Now, there are many types of legal action in tort for HIV infection, such as negligence, battery,fraud, misrepresentation and emotional distress.A thorough discussion on each type of claim is beyond the scope of this article.However, the focus of discussion of this article is the cause of action that can be taken under the law of tort by a person who was sexually infected with HIV in order to seek damages.